Cultural Wedding Rituals Among Batak Toba Millennials and Gen Z: Perceptions in the Modern Era - An Ethnographic Study - Tiyanda Hanti Arum Kusuma; Rizki Agung Ramadani; Rinta Agustiani Dwiputri; Jerry Heikal (CV. ULIL ALBAB CORP, 2025)
Indonesia has many different ethnic groups. Among them, the Batak people stand out. Batak weddings are known for being long and elaborate, but with modern times, things are changing. Modernization has made Batak wedding ceremonies more convenient and has changed the way people think, with many preferring practicality. This study explores the perspectives and experiences of the Batak community regarding the traditional Batak wedding ceremony and its relevance in modern times. A qualitative research method with an Ethnography approach was employed. Through five interview questions, the study aims to understand whether the Batak wedding rituals are perceived as challenges or advantages, whether the process remains relevant, and how individuals respond to the idea of shorter and more practical wedding ceremonies. Purposive sampling was used to select Generation Millennial and Generation Z respondents for in-depth interviews.The interview results from four respondents indicate that despite the complex and time-consuming nature of the Batak wedding rituals, the Batak community still regards them as a sacred cultural heritage. Respondents believe that the lengthy process brings benefits such as a deeper appreciation for marriage and lower divorce rates. The two generations share the same views on traditional marriage, with shared values of the sacredness of marriage and preserving cultural heritage. Overall, this study highlights the importance of preserving and passing down Batak wedding traditions while accommodating societal changes.